1976
DOI: 10.1210/jcem-43-3-523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphorus Supplementation on Serum Parathyroid Hormone and Bone Morphology in Osteoporosis

Abstract: The effect of phosphorus (inorganic phosphate) supplementation was studied in seven postmenopausal women with osteoporosis. Prior to supplementation, all chemical parameters studied in serum and urine were normal. Bone density was below the fifth percentile for age in all but one patient, and the percentage of bone surface involved in resorption was higher than normal. During administration of the phosphorus supplement, fasting serum concentrations of calcium and immunoreactive parathyroid hormone showed no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Black and Asian people and older people may be susceptible to bone resorption as a result of high phosphorus intakes, as they are more susceptible to hypovitaminosis D, which decreases the absorption of calcium, and phosphorus has been shown to influence the parathyroid-vitamin D axis, causing an increase in serum calcium levels via bone resorption. [32][33][34] …”
Section: General Information and Effect Of Phosphorus Toxicitymentioning
confidence: 99%
“…Black and Asian people and older people may be susceptible to bone resorption as a result of high phosphorus intakes, as they are more susceptible to hypovitaminosis D, which decreases the absorption of calcium, and phosphorus has been shown to influence the parathyroid-vitamin D axis, causing an increase in serum calcium levels via bone resorption. [32][33][34] …”
Section: General Information and Effect Of Phosphorus Toxicitymentioning
confidence: 99%
“…In postmenopausal women, PTH but not 1,25(OH)2D3 levels increased rapidly with phosphate supplementation, but this did not affect bone formation or resorption (Brixen, Nielsen, Charles & Moskilde, 1992), though whether this difference in response was due to differences in Ca intake is not clear, since no information on this was given. In an earlier study Goldsmith, Jowsey, Dube, Riggs, Arnaud & Kelly (1976) reported that increasing phosphate intake for 3-30 months decreased bone formation and increased bone resorption in osteoporotic patients. Examination of the data indicates, with one exception, that small 9-2 elevations in serum PTH at 3-4 months were only seen where the dietary Ca: P ratio was less than 1:2 and Ca intake was low (below 0-8 g day-1).…”
Section: Performancementioning
confidence: 95%
“…Studies carried out on healthy subjects with doses of 3 g/day of phosphorus supplemented on top of a standard diet containing 1.7 g phosphorus/day, appeared to show similar incidences of diarrhoea and few effects on bone resorption or bone turnover (Grimm et al, 2001). In a study on the effect of oral phosphate therapy on 7 postmenopausal women with osteoporosis (a daily dose of approximately 1 g of phosphorus for more than 12 months), the number of bone resorption surfaces was reported to increase in all patients while the number of bone-forming surfaces decreased (Goldsmith et al, 1976).…”
Section: Effect Of Phosphorus Intakementioning
confidence: 98%